Hepatitis B Virus Replication Is Associated with an HBx-Dependent Mitochondrion-Regulated Increase in Cytosolic Calcium Levels - McClain, Stephanie L. (American Society for Microbiology (ASM), 2007)
The nonstructural hepatitis B virus (HBV) protein HBx has an important role in HBV replication and in HBV-associated liver disease. Many activities have been linked to HBx expression; however, the molecular mechanisms underlying many of these activities are unknown. One proposed HBx function is the regulation of cytosolic calcium. We analyzed calcium levels in HepG2 cells that expressed HBx or replicating HBV, and we demonstrated that HBx, expressed in the absence of other HBV proteins or in the context of HBV replication, elevates cytosolic calcium. We linked this elevation of cytosolic calcium to the association of HBx with the mitochondrial permeability transition pore.